2018
DOI: 10.1101/370296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Illuminating spatial A-to-I RNA editing signatures within the Drosophila brain

Abstract: Significance StatementA fundamental question in contemporary neuroscience is how the remarkable cellular diversity required for the intricate function of the nervous system is achieved. In this manuscript, we bridge the gap between a cellular machinery that is known to diversify the transcriptome and the existence of distinct neuronal populations that compose Drosophila brain. Adenosine-to-inosine (A-to-I) RNA-editing is a ubiquitous mechanism that generates transcriptomic diversity in cells by recoding certai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 78 publications
3
23
0
Order By: Relevance
“…To explore the connection between transcriptional programs in NPFR neurons and behavior, we used a recently generated dataset from our lab consisting of RNA sequences from several neuronal populations in the brain, that were obtained by immunoprecipitation of genetically tagged nuclei (INTACT method) 8 . The dataset included 10 neuronal populations known to regulate behavior and physiology: dopaminergic neurons ( TH-Gal4 ), octopaminergic neurons ( Tdc2-Gal4 ), serotonergic neurons ( TRH-Gal4 ), NPF neurons ( NPF-Gal4 ), NPF-receptor neurons ( NPFR-Gal4 ), mushroom bodies ( OK107-Gal4 ), Corazonin neurons ( CRZ-Gal4 ), Dh44 neurons ( CRF orthologue DH44-Gal4 ), fruitless-expressing neurons ( Fru-Gal4 ), and all neurons ( Elav-Gal4 ).…”
Section: Resultsmentioning
confidence: 99%
“…To explore the connection between transcriptional programs in NPFR neurons and behavior, we used a recently generated dataset from our lab consisting of RNA sequences from several neuronal populations in the brain, that were obtained by immunoprecipitation of genetically tagged nuclei (INTACT method) 8 . The dataset included 10 neuronal populations known to regulate behavior and physiology: dopaminergic neurons ( TH-Gal4 ), octopaminergic neurons ( Tdc2-Gal4 ), serotonergic neurons ( TRH-Gal4 ), NPF neurons ( NPF-Gal4 ), NPF-receptor neurons ( NPFR-Gal4 ), mushroom bodies ( OK107-Gal4 ), Corazonin neurons ( CRZ-Gal4 ), Dh44 neurons ( CRF orthologue DH44-Gal4 ), fruitless-expressing neurons ( Fru-Gal4 ), and all neurons ( Elav-Gal4 ).…”
Section: Resultsmentioning
confidence: 99%
“…While RNA sequence and structure are critical determinants of editing levels, studies querying tissue-specific and developmental-stage-specific editing levels show that the level of editing at the same editing site can vary greatly between individuals and tissues. These changes do not always correlate with ADAR mRNA or protein expression, suggesting a complex regulation of editing events by factors other than ADAR proteins (Sapiro et al, 2019; Tan et al, 2017; Wahlstedt et al, 2009). Recently, an analysis of proteins with an RNA-binding domain profiled by ENCODE suggested that RNA-binding proteins play a role in RNA editing regulation.…”
Section: Introductionmentioning
confidence: 96%
“…Additional promiscuous RNA editing occurs in long dsRNAs formed by inverted repetitive elements in both mammals and Drosophila; in humans this additional ADAR RNA editing occurs at millions of sites, mostly non-specifically and at low efficiency in Alu dsRNA hairpins embedded in protein-coding transcripts [3][4][5] . Unlike DNA mutations, RNA editing usually changes only some proportion of the transcripts of particular genes, and editing levels at individual sites can be different in different tissues and developmental stages [5][6][7][8] , due to different ADAR expression levels and other tissue-specific factors. Thus, RNA editing is a powerful tool that can over-write and enrich the genomically encoded information during the process of gene expression.…”
mentioning
confidence: 99%